WAYS TO IMPROVE THE EFFECTIVENESS OF THE CLASS LEADER'S EDUCATIONAL ACTIVITIES - Mamarajabova Yulduz Chorshanbi qizi; Bobomurodov Sirojiddin (American Journals, 2023)
Ways to improve the effectiveness of the class leader's educational activities, to have a conscious attitude to academic work and to be responsible for it approach, improving the quality of students' knowledge and establishing discipline in the classroom is highlighted.
Keywords: educational work, effective, determination, criterion, methodology, identification result, healthy generation, dedication.